Lobbying in the European Union
XI, 459 p. 26 illus., 18 illus. in color.
Keywords: This book sheds new light on how lobbying works in the European Union. Drawing on the first-hand professional experience of lobbyists, policymakers, and corporate and institutional stakeholders, combined with a sound academic foundation, it offers insights into successful lobbying strategies, such as how alliances are formed by interest groups in Brussels. The authors present key case studies, e.g. on the shelved EU-US trade deal Transatlantic Trade and Investment Partnership (TTIP), lobbying scandals, and the role of specific interest groups and EU Think-Tanks. Furthermore, they highlight efforts to improve transparency and ethical standards in EU decision-making, while also underscoring the benefits of lobbying in the context of decision-making. Understanding the tools and techniques of effective lobbying, as well as the dynamics and trends in EU lobbying, will allow professionals involved in the lobbying process, such as policymakers and corporate and institutional stakeholders, to improve their performance and achieve better results when pursuing their respective interests.